Evaluation of the incidental and planned activity questionnaire (IPEQ) for older people - Delbaere, Kim; Hauer, Klaus; Lord, Stephen R. (British journal of sports medicine, 2010)
OBJECTIVE: There is a need for a measure of physical activity that assesses low, basic and high-intensity activities suitable for use in ageing research including falls prevention trials. This study performed a formal validation of the incidental and planned activity questionnaire (IPEQ) by investigating its overall structure and measurement properties. - DESIGN: Cross-sectional survey. - SETTING: Community sample. - PARTICIPANTS: 500 older people (mean age 77.4 years, SD 6.08). - MAIN OUTCOME MEASURES: The IPEQ was administered as part of a longer assessment in two different postal self-completion formats; one for estimating physical activity during the past week (IPEQ-W) and one for estimating average weekly physical activity over the past 3 months (IPEQ-WA). Test-retest reliability was assessed by the re-administration of the instruments one week later in a subsample of 80 respondents. - RESULTS: Both IPEQ versions had good measurement properties, but overall the IPEQ-WA performed better than the IPEQ-W. Rasch analyses indicated the IPEQ-WA had an excellent overall fit. Analysis of the internal structure supported the unidimensionality of the scale with an acceptable internal consistency. The content representation of the items revealed three categories (low, moderate and high levels of physical activity), with a good contribution of items by threshold. The IPEQ-WA had excellent test-retest reliability, intraclass correlation coefficient 0.87) and was able to discriminate differences in physical activity levels between groups differentiated by sex, age and fall risk factors. - CONCLUSIONS: The IPEQ has excellent psychometric properties and assesses the level of physical activity relating to both basic and more demanding activities. Further research is required to confirm sensitivity to change.
Published Online First 26 May 2009
Gesehen am 05.01.2024